Host genetic susceptibility to human tuberculosis. - Bellamy, R; Hill, A (1998)
Convincing evidence exists that host genes influence the outcome of infection in human tuberculosis. We are employing two complementary strategies to find the genes involved: a linkage-based, comprehensive genome screen and an association-based candidate gene study. In a genome screen of 282 markers on 92 affected sib pairs we have found evidence of co-segregation of disease with five markers, but further studies are required to replicate these results. The absence of a single strongly linked marker demonstrates that susceptibility to human tuberculosis is not controlled by a single major gene. Using a candidate gene approach investigating over 400 tuberculosis cases and 400 ethnically matched healthy controls we have found evidence that NR AMP1 and vitamin D receptor gene (VDR) polymorphisms are associated with tuberculosis. It is hoped that by identifying the genes that account for why only a minority of those exposed to tuberculosis develop disease, we will develop new insights into potential therapeutic and preventative strategies.